Management of clinical teaching for nursing students in the Department of Cardiothoracic Surgery under the COVID-19 epidemic (新型冠状病毒肺炎疫情下心胸外科实习护士临床护理带教的管理) - LI Pengping (李鹏萍); SUN Yulian (孙玉莲); WANG Hongdan (王虹丹); HONG Liping (洪丽萍); WU Haiyun (吴海韵); YE Jiajia (叶佳佳) (Association of Integrative Nursing, 2022)
This paper summarized the management of clinical teaching for nursing students in the Department of Cardiothoracic Surgery under the COVID-19 epidemic. By revising a teaching plan for nursing students, new teaching methods such as Wechat platform-based lecture, questionnaire survey, online Conference by Tencent APP were adopted. Course lectures focused on the COVID-19 prevention, common diseases in the Department of Cardiothoracic Surgery, common types of surgery and postoperative nursing. Multiple approaches were provided to improve the nursing students' awareness on cardiothoracic diseases and key issues of postoperative nursing, and improve the quality of clinical teaching. (总结新型冠状病毒肺炎疫情下心胸外科实习护士临床带教管理策略。通过修订实习护士的培训内容, 新增企业微信授课、调查问卷、腾讯会议等教学方法, 重点讲解新型冠状病毒肺炎疫情下防护知识、心胸外科常见疾病、常见手术方式及术后护理, 提高实习护士对心胸外科疾病的认识, 帮助掌握术后护理常规, 关注实习护士的心理状况, 提升护理教学质量。)